Pitting Oedema in a Patient with Lumbar Disc Herniation: Case report of an unusual association - Homa Sadeghian; Rouzbeh Motiei-Langroudi (Sultan Qaboos University Medical Journal, 2018)
Oedema refers to the excessive accumulation of fluid within intercellular tissues as a result of disequilibrium between the capillary hydrostatic and oncotic pressure gradients. Lumbar disc herniation (LDH) commonly causes lower back pain and radicular leg pain. We report a 57-year-old female who presented to the neurosurgery clinic of the Bam University of Medical Sciences, Bam, Iran, in 2015 with pain and pitting oedema in the bilateral lower extremities. Magnetic resonance imaging confirmed a diagnosis of LDH of the L3–L4 and L4–L5 vertebrae. The patient subsequently underwent a bilateral laminotomy and foraminotomy of the involved vertebrae to relieve her pain. Following the surgery, there was a complete resolution of the LDH-related symptoms as well as the oedema. Although LDH has never before been associated with oedema, it may nevertheless cause lower limb oedema in exceptional and rare cases, as highlighted in this patient.